2020
DOI: 10.1055/s-0040-1709180
|View full text |Cite
|
Sign up to set email alerts
|

Subintermeniscal Ligament Pullout Suture Technique for Anterior Cruciate Ligament Avulsion Fracture Fixation—AIIMS Technique

Abstract: Many methods have been described, including pullout suture technique, for arthroscopic fixation of displaced tibial eminence fracture. We are describing our technique of pullout suture, which is a modification of previously described techniques. We passed two sutures arthroscopically through anterior cruciate ligament (ACL) just above the avulsed fragment and then pulled them out through medial and lateral bone tunnel in anterior aspect of crater in tibial plateau. The third suture passed through ACL was pulle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Despite variations in fixation methods, both high-strength sutures and suture buttons are popular implant choices. 1,8,15,21,24 The findings of the current study also supported the use of suture fixation for tibial avulsion fractures. We believe that there will be a trend toward developing fixation techniques using suture-related fixation methods in the future.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Despite variations in fixation methods, both high-strength sutures and suture buttons are popular implant choices. 1,8,15,21,24 The findings of the current study also supported the use of suture fixation for tibial avulsion fractures. We believe that there will be a trend toward developing fixation techniques using suture-related fixation methods in the future.…”
Section: Discussionsupporting
confidence: 80%
“…Several newly proposed techniques for tibial avulsion fracture have been developed recently. 1,8,15,21,24 It is worth noting that these newly developed methods were all suture-related fixation techniques. Despite variations in fixation methods, both high-strength sutures and suture buttons are popular implant choices.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two in five adolescents were found to have an affected limb that was 10 mm longer than the healthy side at final follow-up. Because pull-out sutures are easier, many other authors have taken this approach and obtained good results, with some authors knotting the sutures pulled out of the tibial tunnel at the tunnel opening outside the joint ( 20 , 21 ), or fixing them outside the joint with partially threaded cancellous bone screws (6.5 mm) ( 22 ), or by knotting the suture after passing it through a 3-hole titanium plate ( 23 ). In general, the more sutures with tibial tunnels, the better the fracture reduction, particularly in those fragmented fractures.…”
Section: Pull-out Suturesmentioning
confidence: 99%